Pengaruh Kepemimpinan, Inovasi, dan Pembelajaran Organisasi terhadap Performa Individu dan Kelompok: Sebuah Kajian Literatur - Asbari, Masduki; Novitasari, Dewiana (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to explore the linkages between transformational leadership, innovation, and organizational learning in improving individual and group performance. This study uses a narrative literature review approach to analyze relevant studies, with research data coming from indexed academic literature over the past ten years. The analysis focused on identifying the relationships, mediating and moderating factors among the three elements. The results show that transformational leadership has a significant impact on individual performance, both directly and through the mediation of innovation and organizational learning. Innovation acts as a catalyst that strengthens the relationship between leadership and performance, while organizational learning helps improve adaptation to technological change and external dynamics. The implications of these findings include the importance of developing an adaptive and innovative organizational culture, particularly in the education sector. In conclusion, this study makes significant theoretical and practical contributions by offering a new conceptual framework for understanding the interaction between leadership, innovation and organizational learning. The findings are relevant to support managerial strategies in creating a collaborative, innovative and sustainable work environment in the digital era.